Genotypes, phenotypes and whole genome sequence: Approaches from the My Life Our Future haemophilia project. (May 2018) - Konkle, B. A.; Johnsen, J. M.; Wheeler, M.; Watson, C.; Skinner, M.; Pierce, G. F.; ,
Abstract: Introduction: Information from the genes encoding factor VIII ( F8 ) and IX ( F9 ) is used in reproductive planning and to inform inhibitor formation, bleeding severity and response to therapies. Advances in technology and our understanding of the human genome now allows more comprehensive methods to study genomic variation and its impact on haemophilia. Aims: The My Life Our Future (MLOF) programme was begun in 2012 to provide genetic analysis and to expand research in haemophilia through a research repository. Methods: MLOF enrolled haemophilia A and B patients followed at haemophilia treatment centers in the U.S., including, since 2015, known and potential genetic carriers. Initial F8 and F9 DNA analysis was performed utilizing a next generation sequencing approach which allowed simultaneous detection of F8 inversions and other variants. Candidate variants were confirmed using a second method and multiplex ligation‐dependent probe amplification was used to detect structural variants. Results: The initial phase of MLOF completed enrollment in December 2017 with 11, 356 patients, genetic carriers, and potential carriers enrolled. In the 9453 subjects in whom analysis is complete, 687 unique previously unreported variants were found. Simultaneous sequencing of the F8 and F9 genes resulted in identification of non‐deleterious variants previously reported as causative in haemophilia. DNA from 5141 MLOF subjects has undergone whole genome sequencing through the NHLBI TOPMed programme of the U.S. NIH. Conclusion: MLOF has provided genetic information for patients and their families to help inform clinical care and has established a repository of data and biospecimens to further advance haemophilia research.